Length-weight relationship and condition factor of Pterygoplichthys pardalis(Pisces: Loricariidae) in Malaysia Peninsula. - Samat, Abdullah; Md. Nor, Shukor; Abd. Ghaffar, Mazlan; Arshad, Aziz; Md. Yusoff, Fatimah (INSInet Publication, 2008)
The Pterygoplichthys pardalis in the Langat River of Malaysia Peninsula was studied for its length-weight relationships and condition factor for the period of August 2003 to October 2004. It was revealed that P. pardalis has the allometric growth with b = 2.538 ± 0.039 and a = 0.040 ± 0.006(n = 928). The condition factor (K) for P. pardalis ranged between 1.125 and 8.802. There was no clear pattern showed in both growth parameters for the period of the study, suggesting that there was no significant influence of dry and wet season on to the fish. The best fish condition was recorded for those individuals with length of between 30 and 40 cm (TL) that was coincided with the maturation stage of the fish.